Advanced Interatrial Block Predicts Recurrence of Atrial Fibrillation and Ischemic Stroke in Elderly Patients With Hypertension - Wang, Haijun; Cai, Lili; Guo, Yan; Shuai, Li; Shi, Yang; Si, Quanjin (Frontiers in Physiology, 2022)
Background: This study aimed to investigate whether advanced interatrial block (IAB) is a predictor of recurrent atrial fibrillation (AF) and/or ischemic stroke in elderly patients with AF and hypertension. Methods and objectives: Five hundred and sixteen elderly inpatients (mean age 85.53 ± 9.08 years; 5.43% women) with concurrent paroxysmal AF and hypertension were enrolled in this retrospective observational study. Data on comorbidity, medication, digital electrocardiograms (ECG), and outcomes were obtained from the medical records and follow-up examinations. IAB was classified as partial IAB or advanced IAB according to 12-lead surface ECG analysis on admission. Advanced IAB was defined as a maximum P wave duration of >120 ms with biphasic (±) morphology in leads II, Ⅲ, and aVF by two blinded investigators. The endpoints were recurrent AF and ischemic stroke. Results: We enrolled 120 patients (23.26%) with partial IAB and 187 (36.24%) with advanced IAB. The mean follow-up duration was 19 months. A total of 320 patients (62.02%) developed AF recurrence, and 31 (6.01%) experienced ischemic stroke. Significant predictors of advanced IAB in multivariate analysis were older age (>80 years), increased left atrial diameter (>40 mm), and being overweight (body mass index >25 kg/m2). In the multivariable comprehensive Cox regression analyses, partial IAB was associated with AF recurrence. Advanced IAB was an independent predictor of increased risk of AF recurrence and ischemic stroke. Conclusion: Both partial and advanced IAB are associated with AF recurrence in elderly patients with hypertension. Furthermore, advanced IAB is an independent predictor of ischemic stroke.